The Insight of In Silico and In Vitro evaluation of Beta vulgaris phytochemicals against Alzheimer's disease targeting acetylcholinesterase. - Sidra Rehman; Usman Ali Ashfaq; Muhammad Sufyan; Imran Shahid; Bushra Ijaz; Mureed Hussain (PLoS ONE)
B. vulgaris extracts possess antioxidant, anti-inflammatory along with its role in improving memory disorders. Subsequently, in vitro and in silico studies of its purified phytochemicals may expand complementary and alternative Alzheimer's therapeutic option. Super activation of acetylcholinesterase enzyme is associated explicitly with Alzheimer's disease (AD) ultimately resulting in senile dementia. Hence, acetylcholinesterase enzyme inhibition is employed as a promising approach for AD treatment. Many FDA approved drugs are unable to cure the disease progression completely. The Present study was devised to explore the potential bioactive phytochemicals of B. vulgaris as alternative therapeutic agents against AD by conducting in vitro and in silico studies. To achieve this, chemical structures of phytochemicals were recruited from PubChem. Further, these compounds were analyzed for their binding affinities towards acetylcholinesterase (AChE) enzyme. Pharmacophoric ligand-based models showed major characteristics like, HBA, HBD, hydrophobicity, aromaticity and positively ionizable surface morphology for receptor binding. Virtual screening identified three hit compounds including betanin, myricetin and folic acid with least binding score compared to the reference drug, donepezil (-17 kcal/mol). Further, in vitro studies for anti-acetylcholinesterase activity of betanin and glycine betaine were performed. Dose response analysis showed 1.271 μM and 1.203 μM 50% inhibitory concentration (IC50) values for betanin and glycine betaine compounds respectively. Our findings indicate that phytoconstituents of B. vulgaris can be implicated as an alternative therapeutic drug candidate for cognitive disorders like Alzheimer's disease.